2008
DOI: 10.1262/jrd.19116
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c Upregulation during Capacitation and Spontaneous Acrosome Reaction Determines the Fate of Pig Sperm Cells: Linking Proteome Analysis

Abstract: Abstract.To identify the mechanisms underlying capacitation, we undertook a high-resolution differential proteomic analysis of pig sperm cells. Two-dimensional gel electrophoresis and subsequent MALDI-TOF mass spectrometry analyses led to identification of 56 differentially expressed proteins. After induction of capacitation in vitro, the wellestablished markers of the capacitation (lactadherin P47, acrosomal protein SP-10 precursor, prohibitin, proteasomes, DJ-1 protein and arylsulfatase-A) and TCA cycle prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 62 publications
5
23
0
Order By: Relevance
“…Following ejaculation, Eno1, ATP synthase, and tubulin regulate the sperm capacitation. Besides, a prior study demonstrated that sperm undergoing capacitation displayed increased expression of Eno1 (Choi et al, 2008). The level of sperm motility required in the female reproductive tract is determined by ODF2, PGK2, LDHC, DNAJB13, Sp17, and tubulin.…”
Section: Iv) Cell Signallingmentioning
confidence: 97%
“…Following ejaculation, Eno1, ATP synthase, and tubulin regulate the sperm capacitation. Besides, a prior study demonstrated that sperm undergoing capacitation displayed increased expression of Eno1 (Choi et al, 2008). The level of sperm motility required in the female reproductive tract is determined by ODF2, PGK2, LDHC, DNAJB13, Sp17, and tubulin.…”
Section: Iv) Cell Signallingmentioning
confidence: 97%
“…They include the ubiquitin activating enzyme UBE (Baker et al 2010), multiple proteasomal subunits (Arcelay et al 2008, Baker et al 2010, the valosine-containing protein, involved in ubiquitinated substrate presentation to the 26S proteasome (Geussova et al 2002), and ubiquitin itself (Arcelay et al 2008). Changes in the electrophoretic migration pattern of several 20S core subunits were observed by 2D electrophoresis of capacitated versus non-capacitated boar spermatozoa (Choi et al 2008).…”
Section: Role Of the Ups In Sperm Capacitationmentioning
confidence: 99%
“…Also development and capacitation of mammalian sperm are accompanied by expression of several marker proteins including MDH and isocitrate dehydrogenase (representatives of TCA cycle), and several other proteins like lactadherin P47, acrosomal protein SP-10 precursor, prohibitin, DJ-1 protein, arylsulfatase-A, and cytochrome c (CHOI et al, 2008). At least expression of cytochrome c appears to be regulated via p53 pathway and may be involved in decision developmentallylinked programmed cell death or further spermiogenesis.…”
Section: Developmental Aspects Of Mdh Action and Functionsmentioning
confidence: 99%